Bioadhesive Gauze Embedded with Chitosan-Butein Bioconjugate: A Redox-Active pH Sensor Platform - Vinoth Krishnan; Venkatachalam Ananth; Jayasudha Velayutham; Pandiaraj Manickam; Murugan Veerapandian (Biosensors, 2022)
With the ever-growing global wound care market, demand for robust redox-active healthcare material is obvious for the construction of wearable sensor platforms. Surface reactive functional group-rich material like chitosan holds huge potential for electrochemical biosensor application. Herein, a metal-free redox-active chitosan–butein (CSB) bioconjugate is processed into epidermal bioadhesive electrode material useful for pH sensors promising toward wound site analysis. A two-electrode system devised for conducting carbon-reinforced silver chloride paste and CSB-modified carbon/silver chloride matrix was used as a reference and working electrodes, respectively. Dimensions of working and reference electrodes (4 mm) were designed by 2D cutter plotter-assisted stenciling. The cross-sectional topology of the constructed adhesive CSB-sensor platform exhibits an average surface thickness of 183 ± 2 μm. Cyclic voltammetric analysis revealed the inherent 2e−/2H+ transfer attributed to the catechol OH groups of graft polymerized CSB modified on adhesive gauze. As-fabricated modified electrode substrates exhibit distinguishable potential differences with respect to electrolytes of varied pH (between 5 to 9), promising for wound site analysis.